2010
DOI: 10.1089/cyber.2009.0345
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Computer Experiences and Attitudes of Preservice Mathematics Teachers: New Evidence from Turkey

Abstract: This study aimed to investigate the experiences of pre-service mathematics (PSM) teachers with computers and their attitudes toward them. The Computer Attitude Scale, Computer Competency Survey, and Computer Use Information Form were administered to 180 Turkish PSM teachers. Results revealed that most PSM teachers used computers at home and at Internet cafes, and that their competency was generally intermediate and upper level. The study concludes that PSM teachers' attitudes about computers differ according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…According to the results of the gender-related meta-analysis study by Whitley (1997), gender differences in computer-related behaviors are small. Likewise, Birgin, C ¸atlıo glu, G€ urb€ uz, and Aydın (2010) claim that the gap between genders is narrowing, on account of increasing computer ownership and more pre-service mathematics teachers' using computers regardless of gender. However, Yuen and Ma (2002) found that there are significant gender differences in computer acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the gender-related meta-analysis study by Whitley (1997), gender differences in computer-related behaviors are small. Likewise, Birgin, C ¸atlıo glu, G€ urb€ uz, and Aydın (2010) claim that the gap between genders is narrowing, on account of increasing computer ownership and more pre-service mathematics teachers' using computers regardless of gender. However, Yuen and Ma (2002) found that there are significant gender differences in computer acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some of the results of studies conducted at different period of time and disciplines supported the assumption that it is difficult to change the cognitive characteristics of individuals such as attitude, interest, and level of concern in a short period of time (Gönen, Kocakaya, & İnan, 2006). However, long-term CAI implementations (Baki & Çakıroğlu, 2011;Birgin et al, 2010;Erbaş & Yenmez, 2011;Güven, 2002;Helvacı, 2010;Pilli & Aksu, 2013;Seo & Bryant, 2009;Ubuz et al, 2009;Yıldız, 2009) have proved to be positively influential on students' attitudes and views toward mathematics and geometry.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Birgin, Çatlıoglu, Gürbüz, and Aydın (2010) investigated the relationship between experiences of pre-service mathematics teachers with computers and attitudes towards them. They concluded that ''teachers' attitudes towards computers differ according to their years of study, computer ownership, level of computer competency, frequency of computer use, computer experience, and whether they had attended a computer-aided instruction course'' (p. 512), thus supporting the relationship and its direction suggested by IMBP.…”
Section: Theoretical Frameworkmentioning
confidence: 99%